PEMBANGUNAN SISTEM PENYEDIAAN AIR BERSIH UNTUK MASJID RAUDHATUL JANNAH DI PONDOK PESANTREN MIFTAHUL ULUM KUBU RAYA - Dian Perwita Sari; Muhammad Subhansyah Ikram; Dewi Ria Indriana; Estar Putra Akbar; Caesar Destria (LPPM Universitas Abdurrab, 2025)
This Community Service Program (PPM) was initiated in response to the needs of both the general public and the Miftahul Ulum Islamic Boarding School for adequate facilities and infrastructure to support clean water usage, particularly for religious practices such as ablution (wudu). The aims of this PPM activity is to develop a Clean Water Installation at Raudhatul Jannah Mosque, intended specifically for worship purposes. The clean water supply system will also be utilized by one of the facilities at the Miftahul Ulum Islamic Boarding School, located in Sungai Ambangah Village, RT. 03/02, Sungai Raya District, Kubu Raya Regency. The methods applied in this program include the collection of existing condition data and user requirements, planning analysis, water demand calculations, design concept development, and preparation of a cost estimation (Bill of Quantities). The program is scheduled to run over a six-month period, with four months allocated for planning, followed by implementation and handover during the fifth and sixth months. The expected outcomes of this PPM include the completion of design concept drawings, a detailed cost estimation, and the establishment of a Clean Water Supply System at Raudhatul Jannah Mosque with a capacity of 12,000 liters per day, designed to meet the clean water needs of 423 male and female students.